Generalized Variational Inclusion Problem Involving Averaged Operator and Cayley Operator (Journal of Nonlinear Modeling and Analysis, 2026)
In this paper, we consider and study a variational inclusion problem involving averaged and Cayley operators in the context of a Hilbert space. It is shown that our problem is equivalent to a fixed-point equation. We define an iterative algorithm based on a fixed-point formulation to obtain the solution. Our result is supported by a numerical example, computation tables, and a convergence graph are also provided.
Keywords: Cayley operator; averaged operator; variational inclusion; resolved operator